Proteinuric Kidney Diseases: A Podocyte's Slit Diaphragm and Cytoskeleton Approach - Yu, Samuel Mon-Wei; Nissaisorakarn, Pitchaphon; Husain, Irma; Jim, Belinda (Frontiers in Medicine, 2018)
Proteinuric kidney diseases are a group of disorders with diverse pathological mechanisms associated with significant losses of protein in the urine. The glomerular filtration barrier (GFB), comprised of the three important layers, the fenestrated glomerular endothelium, the glomerular basement membrane (GBM), and the podocyte, dictates that disruption of any one of these structures should lead to proteinuric disease. Podocytes, in particular, have long been considered as the final gatekeeper of the GFB. This specialized visceral epithelial cell contains a complex framework of cytoskeletons forming foot processes and mediate important cell signaling to maintain podocyte health. In this review, we will focus on slit diaphragm proteins such as nephrin, podocin, TRPC6/5, as well as cytoskeletal proteins Rho/small GTPases and synaptopodin and their respective roles in participating in the pathogenesis of proteinuric kidney diseases. Furthermore, we will summarize the potential therapeutic options targeting the podocyte to treat this group of kidney diseases.